تقييم ملاحظات هرلد موتسكي على ادِّعاءات نورمان كولدر على موطأ مالك: دراسة مقارنة: (An Evaluation of Harald Motzki's Criticisms about Norman Calder's Views on Malik's Muwatta: A Comparative Study) - إسماعيل جنار; علاء الدين محمد أحمد عدوي (At-Tajdid - Intellectual Refereed Journal, 2025)
Norman Calder is a British orientalist renowned for his research on Islamic law. In his book 'Studies in Early Muslim Jurisprudence', Calder provides a comprehensive study on early Islamic law, and reveals how Islamic law was formed and developed. In this context, he examines the content and the form of some of the early Islamic Law works. One of these works is Imam Malik's Muwatta, which is a significant work for the science of hadith in terms of the comprising narrations from the Prophet (pbuh), his companions, and followers, as well as for Fiqh in terms of comprising the practices of the people of Medina, reflecting the early practices of Fiqh in Islam. However, Calder questions the belonging of this work to Imam Malik and provides evidence for this claim in his book mentioned above. The subject of our study is the criticisms of Harald Motzki, who responded to these claims in his article "The Prophet and the Cat", and the evaluation of these criticisms. Motzki is known for his work on hadith and Islamic law. In his hadith criticism, he applies the "Isnad cum Matn" method to the narrations and criticizes the orientalist views. The study firstly presents Calder's views and then Motzki's responses to these claims and gives the opinion of Muslim scholars are regarding these claims and evaluates how accurate of Motzki's views are. The study followed a descriptive-analytical approach. It also relied on comparative and critical methodologies. The study reached several conclusions, the most important of which is that Calder relied in his claims on the methods and theories of earlier Orientalists, such as the (e silentio) theory, which was described as weak by Motzki and the view of Muslim scholars who dated the compilation of the Muwatta to around 159 AH and attributed it to Imam Malik, considering this attribution historically more accurate. Keywords: Norman Calder, Harald Motzki, Malik, Muwatta, Hadith.